2013
DOI: 10.1186/1476-069x-12-99
|View full text |Cite
|
Sign up to set email alerts
|

Tele-monitoring reduces exacerbation of COPD in the context of climate change–a randomized controlled trial

Abstract: BackgroundA home based tele-monitoring system was developed to assess the effects of heat stress (days > 25°C) on clinical and functional status in patients with chronic obstructive pulmonary disease (COPD).MethodsSixty-two COPD patients (GOLD II–IV) were randomized into a tele-monitoring Group (TG, N = 32) or Control Group (CG, N = 30). Tele-monitoring included 1) daily clinical status (COPD Assessment Test-CAT), 2) daily lung function and 3) weekly 6-minute walk test (6MWT). Duration of monitoring lasted a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(96 citation statements)
references
References 30 publications
1
93
0
2
Order By: Relevance
“…We found that a lower risk for hospital admission among patients using mobile phone applications than that of the usual care group (RR = 0.73 [95% CI, 0.52 to 1.04]). The study by Jehn M [24] found that the hospital admission rates decreased significantly (RR, 0.30 [95% CI, 0.15 to 0.59]). But the heterogeneity in the overall pooled effect is 51.4% (I 2  = 51.4%, p  = 0.04), implying that effect sizes varied across studies.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that a lower risk for hospital admission among patients using mobile phone applications than that of the usual care group (RR = 0.73 [95% CI, 0.52 to 1.04]). The study by Jehn M [24] found that the hospital admission rates decreased significantly (RR, 0.30 [95% CI, 0.15 to 0.59]). But the heterogeneity in the overall pooled effect is 51.4% (I 2  = 51.4%, p  = 0.04), implying that effect sizes varied across studies.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…One study showed a significant reduction (lower predicted FEV1 percentage) in lung function of tele-monitoring intervention groups [24]. However, there was no significant differences found in another study [26].…”
Section: Resultsmentioning
confidence: 99%
“…Simply having COPD was not the cause of the alert, but rather a confluence of factors. Jehn et al [26] explored the effects of heat stress (days warmer than 25°C) on AECOPDs, finding “heat stress negatively impacts clinical and functional status in patients with COPD and makes patients more vulnerable for disease-related morbidity.” In addition, the amount or type of activities of daily living undertaken may positively or negatively influence COPD symptoms, such as dyspnea and fatigue [27]. …”
Section: Discussionmentioning
confidence: 99%
“…All of the studies were conducted on relatively small samples, less than 100 participants each. Some research studies specified the COPD severity stage according to the GOLD guidelines [ 21 - 23 ], whereas other studies included patients in all COPD stages [ 19 , 20 , 24 ]. Furthermore, patients were required to be free from COPD exacerbations for either at least 3 weeks [ 21 ] or one month [ 19 , 20 , 23 , 24 ] to be included in the research studies.…”
Section: Resultsmentioning
confidence: 99%